Christian theology as comparative theology: Towards a radical change of "Method". Issue 4 (2nd November 2022) - Kärkkäinen, Veli‐Matti
Abstract: This essay makes a recommendation for an expansion in the approach and "method" of Christian theology: it proposes Christian theology as comparative theology. In the religiously pluralistic world, it is not sufficient merely to engage other faith traditions as an "auxiliary task." Rather, the comparative task should belong to the "normal" way of doing "basic" Christian theological work. While Christian theology is not subsumed under comparative theology, as it were, the essay argues that without the comparative task, Christian theology may fail its calling in the third millennium.